ANTROPOMETRIA E DINAMOMETRIA EM PORTADORES DE INSUFICIÊNCIA RENAL CRÔNICA QUE NÃO REALIZAM HEMODIÁLISE - Schneider, Juliana; Fassbinder, Tânia R. C.; Wendland, Juliana; Winkelmann, Eliane R.; Sartori, Angela (Salão do Conhecimento, 2013)
Resumo